Website Design for Pineapple-Based MSMEs in Purbalingga Using the Extreme Programming Method (Case Study: Rumah Olahan Nanas Pinne) - Anggraeni, Latifah; Gustalika, Muhamad Azrino (CV. Media Inti Teknologi, 2025)
Background: Rumah Olahan Nanas Pinne is one of the MSMEs in Purbalingga Regency that is engaged in the processing of pineapple-based products. In running its business, this MSME faces obstacles in promoting its products digitally and recording sales reports manually, which hinders operational efficiency.Aims: This study aims to develop a website that can be used as a digital promotional medium and to view sales reports in a more structured manner.Methods: The website system was developed using the Extreme Programming method, which is known for its flexibility and iterative nature, allowing for changes during the development process. System testing was conducted using the blackbox testing method to test the functionality of the system.Result: The website was successfully developed and its functionality runs according to the design with a blackbox testing success rate of 100%.Conclusion: The developed website has been successful in helping to promote products digitally to expand market reach. In addition, this system also helps in viewing sales reports easily and accurately.